MENUMBUHKAN KESADARAN ORANG TUA DALAM MENANAMKAN NILAI MORAL ANAK USIA DINI MELALUI PARENTING EDUCATION - Qadafi, Muammar (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
Parenting education is a very important activity that should be implemented in early childhood education institutions. This activity is an opportunity for teachers to provide enthusiasm and foster awareness of parents to be involved in children's education. This research is a qualitative research with a case study approach carried out at RA Tiara Chandra Yogyakarta. The purpose of this study is to find out how parenting education was carried out in this school and how was the benefits to the develop parents’ awareness to succeed of the program of developing moral values of children. The results of the study showed that parenting education was carried out routinely in the form of training in living values education and monthly parenting to provide refreshment and evaluate programs that have been implemented. There were three groups of activities that had been carried out, namely education, involvement, and empowerment of parents. Parental involvement in developing children's moral values had a significant impact on children's awareness to live up to moral values in their daily life.Keywords: parenting education, moral values, early childhood